The Relevance of Competence-Based Learning and Assessment to the Achievement of Sustainable Development Goal 3: Health and Welfare - Wulansari, Ekawati Rini; Ipol, Dina Chintamy (Journal of English Language and Education, 2025)
This research aims to analyze the relevance of learning Competence-Based Learning in achieving Sustainable Development Goal (SDG) 3, namely towards a healthy life and improving welfare for all.  This research uses qualitative methods to explore the application of CBL in health education and its impact on student health behavior. The results show that a competency-based approach can increase students' understanding of health and well-being, and encourage them to take proactive action in maintaining personal and environmental health. The implementation of CBLA is in line with national education policy which emphasizes the importance of competency development as part of efforts to improve the quality of human resources in Indonesia. Thus, CBLA supports the national education goal of creating individuals who are not only academically intelligent but also have practical skills that can be applied in society. Overall, CBLA makes a significant contribution to the development of competencies needed by students and the workforce, as well as supporting the achievement of broader educational goals. With this approach, education can be more relevant and responsive to the needs of society and the world of work today.